Design Criteria in the Creation of Assistive Products - Tavares, Monica; Henno, Juliana; Pai, Chi-Nan (DAT Journal, 2024)
This article discusses how aesthetic, practical and symbolic criteria can be applied, in a non-mutually exclusive way, to the design of assistive products, to broaden the experience of people with visual, auditory, or motor loss, improving their accessibility and inclusion in their sociocultural context. The design of the great majority of assistive devices prioritizes their functionality, relegating their aesthetic configuration and symbolic value to a secondary level, which reflects the inadequacy of many users of assistive devices in their cultural context. From this perspective, it’s assumed the need to include people as a central point of the design experience. From the four parts in the article, we can understand that there is a guideline to directly or indirectly insert the individual into the production/reception processes of these objects, so that he/she feels able to re-signify such objects, by including attributes of aesthetic uniqueness and symbolic value in them, expanding the person’s identification with the product and his/her belonging to the sociocultural context. Therefore: what resonates with the concept of transformational prosthesis.